2013
DOI: 10.1021/ac400378q
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Analysis of Laser Printed Ink by X-ray Fluorescence and Laser-Excited Plume Fluorescence

Abstract: We demonstrated a minimally destructive two-tier approach for multielement forensic analysis of laser-printed ink. The printed document was first screened using a portable-X-ray fluorescence (XRF) probe. If the results were not conclusive, a laser microprobe was then deployed. The laser probe was based on a two-pulse scheme: the first laser pulse ablated a thin layer of the printed ink; the second laser pulse at 193 nm induced multianalytes in the desorbed ink to fluoresce. We analyzed four brands of black ton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…The forensic analysis of laser printed ink by XRF and plume laser excited atomic uorescence (plume-LEAF) for the determination of ink origin and illicit overprinting was presented by Chu et al 96 Four branded black toner samples were selected that are widely used and similar in composition. Text of various font sizes was printed onto standard copier paper for analysis.…”
Section: Inorganic Chemicals Catalysts and Acidsmentioning
confidence: 99%
“…The forensic analysis of laser printed ink by XRF and plume laser excited atomic uorescence (plume-LEAF) for the determination of ink origin and illicit overprinting was presented by Chu et al 96 Four branded black toner samples were selected that are widely used and similar in composition. Text of various font sizes was printed onto standard copier paper for analysis.…”
Section: Inorganic Chemicals Catalysts and Acidsmentioning
confidence: 99%
“…Due to its ability to provide reliable qualitative and quantitative information about the composition of materials allied with its nondestructive character, XRF has been used in many different fields, such as geology [1], petrology [2], mineralogy [3], archaeology [4], agriculture [5], environmental remediation [6], forensics [7], art conservation [8].…”
Section: Introductionmentioning
confidence: 99%
“…We have used pXRF to analyze laser printed black toners on photocopier paper and Chinese black ink on xuan paper [14,15]. We showed that it is a good screening tool when the analyte elements are abundant (percent range) and when the specimen is optically thick.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the elemental analysis of seal imprints on artwork the inked area is likely to be sparse; and for authentication purposes, the signature elements are probably present at low concentrations. In such cases, we have shown that pXRF is best supplemented by an analytical technique that we named plume-LIF, or PLIF for short [14,15]. PLIF stands for laser-induced-fluorescence of plumes.…”
Section: Introductionmentioning
confidence: 99%